Effectiveness of professional certificate program offered by PNBII / Siti Nurhuda Sukirman - Sukirman, Siti Nurhuda (Faculty of Business and Management, 2008)
This research is a study about the Effectiveness of Professional Certificate Program offered by PNBII. The purpose of this research is to know why this program been offered by PNBII and how did this program is differ from the other education provider in Malaysia. This research is conducted from the way of the institution runs the program to all students that were selected as a respondents to answer the questionnaire. The objectives of this study are to identify which factors that influence most in contributing to the effectiveness of the program) to determine the suitable factor that able to ensure that the program be more effective and final objective is to find out whether this program able to help those students who joined are able to gain benefit from the program. The data been analyzed using the Statistical Package for Social Science (SPSS) software, it can be concluded that this program is effective especially for those who are unemployed in helping them to find the job in finance and investment industry in Malaysia.